2012
DOI: 10.4103/0970-9290.99040
|View full text |Cite
|
Sign up to set email alerts
|

Immediate natural tooth pontic: A viable yet temporary prosthetic solution: A patient reported outcome

Abstract: The concept of immediate pontic placement is surely a viable treatment option and promises an excellent transient esthetic solution for a lost tooth as well as enables good preparation of the extraction site for future prosthetic replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…A previous volumetric study conducted by Nyström et al [13] has shown that a significant amount of resorption in bone grafts took place during the first 6 months after surgery. Lin et al [29] has also reported that most of the resorption of onlay bone grafts took place during the first 6 postoperative months. The results of the previously stated studies were the same as the bone resorption changes of ABBW in the present study.…”
Section: Discussionmentioning
confidence: 96%
“…A previous volumetric study conducted by Nyström et al [13] has shown that a significant amount of resorption in bone grafts took place during the first 6 months after surgery. Lin et al [29] has also reported that most of the resorption of onlay bone grafts took place during the first 6 postoperative months. The results of the previously stated studies were the same as the bone resorption changes of ABBW in the present study.…”
Section: Discussionmentioning
confidence: 96%
“…This treatment options has the major limitation of being only an interim therapy. In a study by Bhandari &Chaturvedi (6) it was reported that out of 15 patients, hundred percent of patients were happy with the esthetics, however, 60% of them were dissatisfied with the function that it provided. The primary problem is apprehension of splint fracture and difficulty while incising.…”
Section: Discussionmentioning
confidence: 99%
“…If the patient's own extracted tooth would have been available for use then it would have been the first choice of the dentist to be used as an option for the replacement. There are several studies in the literature about restorations that were conducted using the patient's own tooth [6,7]. Bhandari et al, reported a case that included a fixed partial denture that was obtained using multiflex orthodontic wire and the patient's own extracted tooth that had been lost due to periodontal reasons [7].…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies in the literature about restorations that were conducted using the patient's own tooth [6,7]. Bhandari et al, reported a case that included a fixed partial denture that was obtained using multiflex orthodontic wire and the patient's own extracted tooth that had been lost due to periodontal reasons [7]. Mengrong et al, reported a case that included a maxillary anterior tooth restoration by using a fiber-reinforced composite with a natural tooth pontic [6].…”
Section: Discussionmentioning
confidence: 99%